Crystal structure, Hirshfeld surface analysis and computational study of bis(2-{[(2,6-dichlorobenzylidene)hydrazinylidene]methyl}phenolato)cobalt(II) and of the copper(II) analogue - Manawar, Rohit B.; Mamtora, Mayank J.; Shah, Manish K.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The title homoleptic Schiff base complexes, [M(C14H9Cl2N2O)2], for M = CoII,(I), and CuII, (II), present distinct coordination geometries despite the Schiff base dianion coordinating via the phenolato-O and imine-N atoms in each case. For (I), the coordination geometry is based on a trigonal bipyramid whereas for (II), a square-planar geometry is found (Cu site symmetry 1). In the crystal of (I), discernible supramolecular layers in the ac plane are sustained by chlorobenzene-C—HO(coordinated), chlorobenzene-C—H(fusedbenzene ring) as well as (fused-benzene, chlorobenzene)–(chlorobenzene) interactions [inter-centroid separations = 3.6460 (17) and 3.6580 (16) A˚ , respectively]. The layers inter-digitate along the b-axis direction and are linked by dichlorobenzene-C—H(fused-benzene ring) and – interactions between fused-benzene rings and between chlorobenzene rings [inter-centroid separations = 3.6916 (16) and 3.7968 (19) A˚ , respectively] . Flat, supramolecular layers are also found in the crystal of (II), being stabilized by – interactions formed between fused-benzene rings and between chlorobenzene rings [intercentroid separations = 3.8889 (15) and 3.8889 (15) A˚ , respectively]; these stack parallel to [101] without directional interactions between them. The analysis of the respective calculated Hirshfeld surfaces indicate diminished roles for HH contacts [26.2% (I) and 30.5% (II)] owing to significant contributions by ClH/HCl contacts [25.8% (I) and 24.9% (II)]. Minor contributions by ClCl [2.2%] and CuCl [1.9%] contacts are indicated in the crystals of (I) and (II), respectively. The interaction energies largely arise from dispersion terms; the aforementioned CuCl contact in (II) gives rise to the most stabilizing interaction in the crystal of (II).